Addressing Educational Inequality in Indonesia: Policy Challenges and Digital Solutions for Disadvantaged Regions - Suarlin; Elpisah M.Pd; Nurfadila MY (CV. Mitkom Indotama, 2026)
This study examines educational inequality in Indonesia, focusing on the most disadvantaged regions, particularly the 3T (terluar, terdepan, tertinggal) areas. The research aims to evaluate the effectiveness of key policies, such as the Merdeka Curriculum and Indonesia Pintar (PIP) program, and assess the role of digital solutions in addressing disparities in educational access and quality. Despite various government initiatives, educational inequality in Indonesia remains persistent, driven by factors including economic constraints, teacher quality, social exclusion, and regional disparities. The study reveals that although some policies and digital solutions have shown promise, major barriers remain, such as inadequate policy implementation, unequal teacher distribution, poor infrastructure, and limited access to technology, particularly in rural areas. The research uses a Systematic Literature Review (SLR) approach to synthesize existing studies from both international and regional perspectives. The findings highlight significant gaps in educational outcomes between urban and rural students, and within the 3T regions, with disparities in years of schooling, literacy rates, and access to higher education. Additionally, while the use of technology in education presents opportunities for bridging educational gaps, issues like digital illiteracy and limited infrastructure hinder its full implementation. This study offers valuable insights into the challenges and solutions for achieving educational equity in Indonesia and provides evidence-based recommendations for policymakers, educators, and communities working to reduce disparities and improve long-term educational outcomes in remote areas.